2016
DOI: 10.1167/16.10.23
|View full text |Cite
|
Sign up to set email alerts
|

The natural statistics of blur

Abstract: Blur from defocus can be both useful and detrimental for visual perception: It can be useful as a source of depth information and detrimental because it degrades image quality. We examined these aspects of blur by measuring the natural statistics of defocus blur across the visual field. Participants wore an eye-and-scene tracker that measured gaze direction, pupil diameter, and scene distances as they performed everyday tasks. We found that blur magnitude increases with increasing eccentricity. There is a vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 62 publications
2
43
0
Order By: Relevance
“…In line with Sprague et al [14], the current results suggest that stronger blurring is more likely to occur when fixation is located on near objects, compared with the situation when fixation is on distal objects. The same authors also concluded that defocus of more than ± 0.5 diopters is highly unexpected.…”
Section: Level Of Defocus Depending On the Scene And The Distributionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with Sprague et al [14], the current results suggest that stronger blurring is more likely to occur when fixation is located on near objects, compared with the situation when fixation is on distal objects. The same authors also concluded that defocus of more than ± 0.5 diopters is highly unexpected.…”
Section: Level Of Defocus Depending On the Scene And The Distributionsupporting
confidence: 91%
“…However, the theoretical approach presented in [13] accounted neither for temporal variations of the scene nor for temporal summation. An experimental approach was implemented by Sprague and colleagues [14], who presented the first procedure to map out the defocus blur from scenes into the eye. The method relied on the disparities detected by stereo cameras but was limited to the central 10° around the fovea and did not include peripheral positions assumed to be important for emmetropisation (20°-40°) [15].…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is based on two main findings: (1) Horizontal disparity is absent from the HM but varies along the VM: stimuli presented above the fixation point have uncrossed disparity and perceived as further away from fixation, whereas stimuli below fixation have crossed disparity and appear closer to fixation. This pattern has been shown both behaviorally in humans (Helmholtz, 1925;Hibbard & Bouzit, 2005;Sprague et al, 2016;Sprague et al, 2015) and neurophysiologically in monkeys (Sprague et al, 2015). 2Blur caused by disparity increases and covers more area as stimulus eccentricity increases (Sprague et al, 2016).…”
Section: Figure 2 Spatial Frequency (Sf) Sensitivity (A)mentioning
confidence: 66%
“…This pattern has been shown both behaviorally in humans (Helmholtz, 1925;Hibbard & Bouzit, 2005;Sprague et al, 2016;Sprague et al, 2015) and neurophysiologically in monkeys (Sprague et al, 2015). 2Blur caused by disparity increases and covers more area as stimulus eccentricity increases (Sprague et al, 2016). Given that these two factors increase with eccentricity, horizontal disparity could be a contributing source to the HVA and VMA and affect their extent.…”
Section: Figure 2 Spatial Frequency (Sf) Sensitivity (A)mentioning
confidence: 74%
“…The human visual system and most cameras have arrays of sensors that are differentially sensitive to long-, medium-, and short-wavelength light. In human vision, the sensitivities of the long-(L), medium-(M), and short-(S) wavelength cones peak at 570, 530, and 445 nm, respectively 13 In the human eye, the change in chromatic defocus between the peak sensitivities of the L and S cones is approximately 1 diopter (D). 1 In many cameras, the sensitivity of the red, green, and blue sensors peak at 590, 530, and 460 nm.…”
Section: Sensing Properties Of Photosensorsmentioning
confidence: 99%